PENGARUH DISIPLIN KERJA DAN MOTIVASI KERJA TERHADAP KINERJA KARYAWAN PADA CV. ADI JAYA MANDIRI - Endah Budiastuti; Faisal Akbar; Evi Novita (Jurnal Ekonomi Manajemen, 2021)
This study aims to determine the effect of work discipline and work motivation on employee performance at CV. Adi Jaya independent. The type of research used in this study uses a quantitative approach with multiple linear regression analysis techniques. The type of data used is primary data obtained through a questionnaire using SPSS for Windows version 17 and observation. Secondary data obtained from company data as well as several books and journals that can be accounted for. The sample in the study was 30 respondents using saturated sampling technique. The results of this study based on the value of R Square indicate that the influence of work discipline and work motivation on the performance of employees of CV. Adi Jaya Mandiri at 0.816 or 81.6%. Which means that the variables of work discipline and work motivation in this study contributed 81.6% to performance. While the remaining 18.4% is explained by other variables not included in this study.